Avaliação das aprendizagens: entre o dito e o praticado - RIBEIRO, Fábio José Alves (2020)
This work, developed as part of the research project titled "Perceptions of Graduates on appraisal of learning in the initial years of Elementary School", aims to identify conceptions and evaluation instruments that permeate the practice of a teacher of the 4th year of Elementary Education of a public school in Belém-PA, based on the studies of Fernandes (2009), Luckesi (2012), Hoffman (2010) and others discussing conceptions of evaluation and instruments used to evaluate. research was carried out in: theoretical study, observations with as north the Observational Matrix of the AERA Project (BORRALHO and LUCENA, 2015), group of discussions, questionnaire application and analysis.The analyzes allow to indicate that the teacher presents discourse compatible with present aspects in the conception of formative evaluation. However, when observing its practice, it was identified pr more initiatives compatible with the design of evaluation as measurement and quantification.